2018
DOI: 10.1017/s1751731118000174
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and metabolomic responses induced in the livers of growing pigs by a short-term intravenous infusion of sodium butyrate

Abstract: Previous studies showed that butyrate played benefit roles in the health and metabolism of animals. However, little information on the effects of butyrate on the metabolism of piglets at the extraintestinal level is available. The present study investigated transcriptomic and metabolomic responses in the livers of pigs to evaluate the effects of intravenous sodium butyrate (SB) on the body's metabolism at the extraintestinal level. A total of 12 Duroc×Landrace×Large White growing barrows (60 days of age) fitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The expression levels of the OXSM , HSD17B8 and ACSF3 genes were downregulated in the subcutaneous fat of the yaks under ES ( q < 0.05). Acetyl-CoA acyltransferase 2 (ACAA2) is the key enzyme in the process of translating acetyl-CoA to fatty acids (4 < n < 16) [ 37 ], and the expression of the ACAA2 gene was downregulated ( q < 0.01) in the subcutaneous fat of the yaks in the ES group. It was inferred that SFA synthesis was inhibited in yaks under ES during the cold season.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of the OXSM , HSD17B8 and ACSF3 genes were downregulated in the subcutaneous fat of the yaks under ES ( q < 0.05). Acetyl-CoA acyltransferase 2 (ACAA2) is the key enzyme in the process of translating acetyl-CoA to fatty acids (4 < n < 16) [ 37 ], and the expression of the ACAA2 gene was downregulated ( q < 0.01) in the subcutaneous fat of the yaks in the ES group. It was inferred that SFA synthesis was inhibited in yaks under ES during the cold season.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Yu et al (2017) [32] reported that oval butyrate changed betaalanine metabolism, alanine metabolism, and cysteine metabolism in d7 and glycine, serine and threonine metabolism in d 21 in the liver of neonatal piglets. In addition, previous research proved that intravenous infusion of SB could change the pathway of glycine, serine and threonine metabolism, beta-Alanine metabolism, and methionine metabolism in the liver of growing piglets [26]. These results suggested that whether oral or intravenous infusion, SB could affect amino acid Differences were analyzed by two-way ANOVA using PROC MIXED with time and SB treatment as the main factors followed by post-hoc analysis in SAS.…”
Section: Effects Of Intravenous Infusion Of Sb On Amino Acid Metabolism Of Growing Pigsmentioning
confidence: 99%
“…Several reports in vitro showed that butyrate could stimulate porcine adipocyte differentiation [20], induce metabolic adaptations [21], and stimulate leptin production in adipocytes [22]. Moreover, researches have found that intravenous injection of SB could increase the secretion of amylase [23], improve structural aspects of intestinal adaptations by increasing proliferation and decreasing apoptosis [24], change the gene expression of the intestine [25] and the liver [26], and remold the composition of intestinal microecology [27] in animal models with intestine injury. Our previous study [26] showed that the infusion of butyrate changed the metabolite profile of the liver in a healthy growing pig model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that 10 days of oral administration of sodium butyrate (SB) alleviates diet-induced obesity and insulin resistance in mice by activating the adiponectin-mediated pathway and stimulating the mitochondrial function in skeletal muscles [ 15 ]. Our previous study showed that short-term intravenous SB infusion modulates the hepatic lipid metabolism by increasing fatty acid transportation and cholesterol metabolism and decreasing fatty acid oxidation [ 16 ]. However, it remains unclear whether systemic butyrate administration differentially impacts the metabolism of different tissues.…”
Section: Introductionmentioning
confidence: 99%